2003
DOI: 10.1007/s00122-002-1026-x
|View full text |Cite
|
Sign up to set email alerts
|

Salt-tolerant mutants in glycophytic salinity response (GSR) genes in Catharanthus roseus

Abstract: The periwinkle Catharanthus roseus shares glycophytic properties of crop plants. To contribute towards an understanding of the glycophytic response to salinity, large populations of M(2) seeds having an origin in nitroso-methyl urea and ethyl methane sulphonate treatments were screened for germination with 250 mM of NaCl. Out of the nine mutant lines so recovered, which tolerated salt stress due to loss of the normal glycophytic salinity response ( GSR), the characteristics of six gsr mutants are reported here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…Similarly, Orabi and Abdelhamid (2014) reported the effect of α-Toc on proline content in the leaves of faba bean plants grown under seawater salinity. These results indicated that high proline is an indicator of intense stress (Ain-Lhout et al, 2001;Rai et al, 2003), while others are of the view that proline at high concentration acts as a osmoprotectant (Taie et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, Orabi and Abdelhamid (2014) reported the effect of α-Toc on proline content in the leaves of faba bean plants grown under seawater salinity. These results indicated that high proline is an indicator of intense stress (Ain-Lhout et al, 2001;Rai et al, 2003), while others are of the view that proline at high concentration acts as a osmoprotectant (Taie et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…Muhammad (2013) showed that the application of K under saline conditions increased proline and total free amino acid concentrations in two maize hybrids. Some researchers have reported that a high proline concentration is a sign of stress (Rai et al, 2003), while others have suggested that high concentrations of proline act as a solute for intracellular osmotic adjustment (Silveira et al, 2003). Maqsood et al (2008) stated that a large number of plant species accumulate proline in response to salinity stress in order to overcome such stress.…”
Section: Statistical Analysis Of the Datamentioning
confidence: 98%
“…Somaclonal variants (Tal, 1990(Tal, , 1993(Tal, , 1994 Induced mutation (Rai et al 2003) Screening tool (Arzani and Mirodjagh 1999) …”
Section: In Vitromentioning
confidence: 99%